The Influence of Brand Image and Promotion on Consumer Purchase Decisions - Purwanti, Dewi; Dipayanti, Kris (Journal of Investment Development, Economics and Accounting, 2025)
The purpose of this study is to determine the influence of brand image and promotion on consumer purchasing decisions of Wardah Renewyou Serum products at Wardah Beauty Store Aeon Mall Bsd South Tangerang. This type of research uses an associative type of research, with a quantitative approach. The population in this study is 211 consumers and the sample in this study is 68 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, and hypothesis tests. The results of this study show Brand Image (X1) and Promotion (X2) has significant effect on Purchase Decision (Y)